1996
DOI: 10.1029/95jd02199
|View full text |Cite
|
Sign up to set email alerts
|

Black carbon formation by savanna fires: Measurements and implications for the global carbon cycle

Abstract: During a field study in southern Africa (Southern African Fire‐Atmosphere Research Initiative (SAFARI‐92)), black carbon formation was quantified in the residues of savanna fires. The volatilization ratios of C, H, N, and S were determined by measuring their contents in the fuel and residue loads on six experimental sites. The volatilization of sulfur (86 ± 8%) was significantly higher than previously reported. Volatilization of H, N, and S was significantly correlated with that of carbon, enabling us to estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 30 publications
2
81
1
Order By: Relevance
“…Despite methodological problems, there is evidence for black soils having been formed as a result of black carbon incorporation in soils through vegetation burning in Australia (Skjemstad et al, 1996(Skjemstad et al, , 1997 and Africa (Kuhlbusch et al, 1996) or through the accumulation of hear thashes in Amazonian Brazil (Terra Preta; Glaser et al, 2001). Although the processes of incorporation and colouring are not yet clearly understood, soil colour (lightness) and amount of aromatic carbon, typical for black carbon, correlate (Spielvogel et al, 2004).…”
Section: Charred Organic Matter As Colouring Agentmentioning
confidence: 99%
“…Despite methodological problems, there is evidence for black soils having been formed as a result of black carbon incorporation in soils through vegetation burning in Australia (Skjemstad et al, 1996(Skjemstad et al, , 1997 and Africa (Kuhlbusch et al, 1996) or through the accumulation of hear thashes in Amazonian Brazil (Terra Preta; Glaser et al, 2001). Although the processes of incorporation and colouring are not yet clearly understood, soil colour (lightness) and amount of aromatic carbon, typical for black carbon, correlate (Spielvogel et al, 2004).…”
Section: Charred Organic Matter As Colouring Agentmentioning
confidence: 99%
“…Using this approach, calculated fire occurrence does exhibit a clear seasonality as a function of drought and litter, and simulated fire return times are reasonable. A parameterization of the transformation of biomass into black carbon, which can be regarded as totally inert at the timescales ORCHIDEE is designed for (a few thousand years at most), has been introduced into the fire subroutine following the work of Kuhlbusch et al [1996].…”
Section: Vegetation Dynamicsmentioning
confidence: 99%
“…Essentially two studies are available (Kuhlbusch and Crutzen, 1995;Kuhlbusch et al, 1996) that used a method based on resistance to thermal oxidation. For savanna fires in South Africa (Kuhlbusch et al, 1996), pre-fire vegetation and litter was approximately 2700 kg ha −1 from which 90% of C was volatilized.…”
Section: Production Of Pycmentioning
confidence: 99%
“…Essentially two studies are available (Kuhlbusch and Crutzen, 1995;Kuhlbusch et al, 1996) that used a method based on resistance to thermal oxidation. For savanna fires in South Africa (Kuhlbusch et al, 1996), pre-fire vegetation and litter was approximately 2700 kg ha −1 from which 90% of C was volatilized. Conversion to BC was 0.5 to 2% (mean 1%) based on prefire C stocks (defined as the ratio BC/CE, where CE is carbon exposed to fire), or 1.3%, based on BC/CO 2 -C. From laboratory burns of 20 non-woody biomass substrates, Kuhlbusch and Crutzen (1995) found that BC/CE was 0.14-2.2%, or 0.15-2.9% as BC/CO 2 -C. For deciduous wood (mean for two substrates), the values were higher, with BC/CE 3.1%, and BC/CO 2 -C 4%.…”
Section: Production Of Pycmentioning
confidence: 99%